Em proveito dos sãos perde o lázaro a liberdade: uma história das políticas públicas de combate à lepra no Brasil (1941-1962) - Maciel, Laurinda Rosa (2007)
The thesis analyzes health public policies concerning Hansen's disease, in Brazil, from 1641 to 1962. These chronological landmarks refer respectively isolation in leprosariums of those affected by disease. The creation of this Service is justified by general reformulation of health services, undertaken by Gustavo Capanema's administration (1934-1945), within a context of establishing the first health policies at nation level. The actions of th e SNL were consolidated in the 1940's and 1950's with the implementation of a prophylaxis policy designed, on one hand to standardize the treatment - the so-called tripod model - and, on the other hand, to meet the regional realities of such a large country. This situation changes along the 1950 decade after the discovery of drugs such as sulphas and antibiotics. The organization of the Campanha Nacional contra a Lepra in 1954, first implemented in Rio de Janeiro and spread in 1959 all over the nation territory, has contributed to change the disease control strategy, based, until then, in hospital isolation. The Departament of Health approved a decree, in 1962, issuing special techinical rules, redirecting the policy by excluding hospital isolation as an adequate prophylaxis for leper.